Faktor Penentu Kejadian Hipertensi Di RSUD TK II Putri Hijau Medan Tahun 2023 - Simatupang, Devina Oktora; Wandra, Toni; Tarigan, Frida Lina; Sitorus, Mido Ester J; Nababan, Donal (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
The purpose of this study was to determine the determinants of hypertension at TK II PutriHijau Hospital in 2023.This research method uses a cross-sectional study. The size of the research sample is 192, obtained by systematic rhythmic sampling. The independent variables in the study consisted of a history of hypertension, high salt consumption, high fat consumption, less consumption of vegetables and fruit, lack of physical activity, smoking habits, and obesity, while the dependent variable was the incidence of hypertension. Data analysis was carried out using univariate, bivariate and multivariate methods.The results showed that there was a significant relationship between history of hypertension, high salt consumption, high fat consumption, less consumption of vegetables and fruit, lack of physical activity, and smoking habits with the incidence of hypertension (p value 0.05), while the obesity variable was not significantly related with hypertension. Multivariately, it was found that five independent variables influenced the incidence of hypertension, namely high consumption of salt (p value= 0.000; OR= 24,2), high consumption of fat (p value= 0.000; OR= 47,7), less consumption of vegetables and fruit (p value = 0.000; OR= 14,1), and lack of physical activity (p value= 0.000; OR= 9,2). So that,the dominantvariable associated with the incidence of hypertension is high consumption of fat, which has a 48 times greater risk of developing hypertension